Developing instruments for measuring the level of early childhood development - I Wayan Gunartha; Tajularipin Sulaiman; Siti Partini Suardiman; Badrun Kartowagiran (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2020)
The aims of the study were to: (1) develop a set of instruments to measure the level of early childhood development (kindergarten group B), and (2) assess the quality of the developed instruments. This study is developmental research. The samples of the study were the students of kindergarten group B. The developed instrument was a set of questionnaires. Instrument testing was carried out in three stages with the number of subjects increased on each stage. The validity analysis of the questionnaire used confirmatory factor analysis (CFA). The reliability estimation of the questionnaire used composite reliability. The results of the study are in the form of instruments for measuring the level of early childhood development, which consists of an instrument to measure religious morality, social-emotional, language, cognitive, and physical-motor development. Based on field study, all instruments have a good fit model, construct validity, and reliability that meet the academic requirements of early childhood education.